ANALISIS TEKANAN PORI LAPANGAN TAPAPA CEKUNGAN JAWA TIMUR UTARA MENGGUNAKAN METODE D-EXPONENT - Ricardo Samosir, Josua
It is necessary to understand the mechanism causing the overpressure, determining the peak overpressure, and predicting the pore pressure. It is also hoped that this will minimize drilling problems in the next development well or the surrounding wells. Overpressure is a term to describe the fluid pressure in the pores of the subsurface rock (pore pressure) which is higher than hydrostatic pressure. The JTU field is located in the North East Java Basin which has five wells namely JTU-3, JTU5, JTU-6, JTU-7 and JTU-8. In the JTU Field, pore pressure estimation is used using the D-Exponent Method using drilling parameter data such as Rate of Penetration, Weight of Bit, RPM, Mud Weight, Equivalent Circulating Density, and Diameter of the tool. The peak of overpressure in the JTU Field is between 2079 feet (633.67 m) to 3099 feet (944.57 m) with a pore pressure of between 1023 psi (7.05 MPa) to 1400 psi (9.8 MPa) which aligned at the intervals of the Wonocolo Formation. The loading mechanism is a mechanism that occurs in the JTU Field supported by an analysis of the sedimentation rate. The deposition rate in the Wonocolo Formation in the five wells has a velocity of 140.118 m/Ma and in the Tuban Shale Formation which is 89.95 m/Ma.